Stackelberg Leadership in a Dynamic Duopoly with Capital Accumulation - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
I propose a dynamic duopoly model where firms enter simultaneously but compete hierarchically à la Stackelberg at each instant over time. They accumulate capacity through costly investment, as in Solow's (1956) growth model.The leader invests more than the followersò as a result, in steady state the leader's capacity and profits are larger than the follower`s Therefore, the present analysis does not confirm Gibrat`s Law, since the individual growth rate is determined by the timing of moves.
Keywords: 330